Understanding Digital Marketing: A Complete Guide to Engaging Customers and Implementing Successful Digital Campaigns - Damian Ryan (USA Kogan Page, 2021)
The world of digital media is constantly changing, as technologies continue to transform the way we interact and communicate on a global scale. In this climate, Understanding Digital Marketing provides a practical, no-nonsense guide to digital marketing, from strategy and digital transformation to best-practice basics and trends. Clear, informative and packed with case studies and examples, it gives an essential grounding in SEO, email marketing, social media, content marketing, performance marketing and much more. This fifth edition of the bestselling Understanding Digital Marketing is fully updated to reflect the latest global developments in the industry. Complete with first-hand accounts of what success in digital marketing looks like, this book is an essential resource for practitioners and students alike. It is now required reading for more than 100 universities and colleges, and has received endorsements from Harvard University, Hult Business School and the Chartered Institute of Marketing.
Keywords: Business; Nonfiction; Technology; Digital marketing; Marketing; (BIN3025-N) Emerging Technologies for the Enterprise